2017
DOI: 10.1039/c7nj01655g
|View full text |Cite
|
Sign up to set email alerts
|

Protection of carbon steel corrosion in 3.5% NaCl medium by aryldiazonium grafted graphene coatings

Abstract: Modification of CS/G by 1,8 ND containing two phenyl rings and two azo groups led to higher protection efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(18 citation statements)
references
References 60 publications
0
18
0
Order By: Relevance
“…9 a, exhibit a diffusion tail in the low-frequency range and a depressed capacitive semicircle in the high-frequency range. The Nyquist plots' depressed capacitive semicircle is caused by the interfacial charge transfer response 65 , 66 . The mass transport mechanism is responsible for the diffusion tail.…”
Section: Resultsmentioning
confidence: 99%
“…9 a, exhibit a diffusion tail in the low-frequency range and a depressed capacitive semicircle in the high-frequency range. The Nyquist plots' depressed capacitive semicircle is caused by the interfacial charge transfer response 65 , 66 . The mass transport mechanism is responsible for the diffusion tail.…”
Section: Resultsmentioning
confidence: 99%
“…The anodic Tafel slope is somewhat larger than that of the cathodic one, and the corrosion potential is slightly displaced anodically, showing that this protective barrier acts mainly as an anodic inhibitor. Graphene layers are well known for the creation of adhered coatings on metal surfaces and affect the slope of anodic and cathodic reactions and hinder the corrosion reaction due to the large specific surface area and excellent mechanical properties [ 11 , 33 ]. These layers may hinder the diffusion of water molecules to the electrode surface [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Graphene is considered as one of the most important classes of modern materials-nanomaterials [ 8 ], which are extensively explored for use in different fields of science from drug delivery [ 9 ] to photovoltaics [ 10 ]; however, graphene remains almost unexplored towards applications aimed at the corrosion inhibition of materials. Only limited scientific research that uses graphene nanomaterials is devoted to corrosion studies [ 11 , 12 , 13 ], and to our knowledge there is no reported study on the use of carboxylated graphene oxide (GO-COOH) as a corrosion inhibitor. The production of nanomaterials is steadily increasing [ 14 , 15 ] using low-cost, abundant natural materials [ 16 ]; therefore, the future use of nanomaterials in corrosion protection is promising.…”
Section: Introductionmentioning
confidence: 99%
“…9 a, demonstrate a depressed capacitive semicircle, followed by a diffusion tail at low frequency. The depressed capacitive semicircle of the Nyquist plots at high frequencies is attributed to the interfacial charge transfer reaction 64 . The diffusion tail at low frequency is attributed to the diffusion process.…”
Section: Resultsmentioning
confidence: 98%